Algorithms for Trigonometric Curves (Simplification, Implicitization, Parameterization) - Hong, Hoon; Schicho, Josef (Journal of symbolic computation, 1998)
A trigonometric curve is a real plane curve where each coordinate is given parametrically by a truncated Fourier series. The trigonometric curves frequently arise in various areas of mathematics, physics, and engineering. Some trigonometric curves can also be represented implicitly by bivariate polynomial equations. In this paper, we give algorithms for (a) simplifying a given parametric representation, (b) computing an implicit representation from a given parametric representation, and (c) computing a parametric representation from a given implicit representation.